Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3389/fimmu.2012.00117
|View full text |Cite
|
Sign up to set email alerts
|

The Fyn-STAT5 Pathway: A New Frontier in IgE- and IgG-Mediated Mast Cell Signaling

Abstract: Mast cells are central players in immune surveillance and activation, positioned at the host–environment interface. Understanding the signaling events controlling mast cell function, especially those that maintain host homeostasis, is an important and still less understood area of mast cell-mediated disease. With respect to allergic disease, it is well established that IgE and its high affinity receptor FcεRI are major mediators of mast cell activation. However, IgG-mediated signals can also modulate mast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 134 publications
0
27
0
Order By: Relevance
“…Moreover, TGFβ1 has many direct effects on mast cells, including increased mMCP-1, and -7 expression, enhanced adhesion and increased migration. However, we and others have also noted that TGFβ1 has suppressive activities on mast cells, including decreased proliferation, FcεRI expression, cytokine production, and reduced c-Kit expression, which some correlated with the induction of apoptosis (reviewed in (46) and (16). How these suppressive activities are carried out has not been determined.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, TGFβ1 has many direct effects on mast cells, including increased mMCP-1, and -7 expression, enhanced adhesion and increased migration. However, we and others have also noted that TGFβ1 has suppressive activities on mast cells, including decreased proliferation, FcεRI expression, cytokine production, and reduced c-Kit expression, which some correlated with the induction of apoptosis (reviewed in (46) and (16). How these suppressive activities are carried out has not been determined.…”
Section: Discussionmentioning
confidence: 79%
“…The decreased phosphorylation of STAT5 in antigen-stimulated PAG-KO cells suggested the reduced production of cytokines and chemokines in such cells (55). Detailed analysis at the protein and mRNA levels showed that, indeed, the levels of three selected cytokines, TNF-␣, IL-6, and IL-13, were significantly reduced in antigenstimulated PAG-KO cells compared with their levels in PAG-WT cells at both the protein and mRNA levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, JAK2 is dispensable in IgE-activated cells, which use FYN for STAT5 phosphorylation (53). Phosphorylated STAT5 serves as a transcription factor for a number of inflammatory genes (55). The reduced transcription of genes for cytokines (TNF-␣, IL-6, and IL-13) and chemokines (CCL3 and CCL4) and the reduced production of TNF-␣, IL-6, and IL-13 in antigenactivated PAG-KO cells could be a direct consequence of impaired STAT5 tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ruxolitinib clearly inhibited MC activity, but its exact intracellular mechanism is not fully elucidated yet. JAK2, and subsequently STAT5, are situated downstream of KIT in MC, and thereby involved in the proliferation and survival of MC . The involvement of the JAK2‐STAT5 pathway in MC degranulation is less well‐described, although there is some evidence available.…”
Section: Discussionmentioning
confidence: 99%
“…Of the different JAK‐ and STAT molecules and signaling pathways currently known, the JAK2‐STAT5 pathway is considered the most important for growth and survival of MC . STAT5 also plays a role in IgE‐mediated MC degranulation, rendering the JAK2‐STAT5 pathway an interesting target for the inhibition of MC activation . In support of this, it has previously been shown that the JAK1/JAK2 inhibitor ruxolitinib attenuates ovalbumin‐induced passive systemic anaphylaxis in mice, while another study demonstrated that several JAK2‐ and STAT5‐inhibitors were able to inhibit activation of canine mastocytoma cell lines .…”
Section: Introductionmentioning
confidence: 89%